BENTUK PENDAMPINGAN KEGIATAN “MATH FUN” PADA TUTOR DAN SISWA SANGGAR INSAN EMAS RUNGKUT (SIER) SURABAYA DALAM MEMOTIVASI MINAT BELAJAR MATEMATIKA - *Ira Wulan Sari; Sri Rejeki Puri Wahyu Pramesthi; Fanny Adibah; Rudi Antonius (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2023)
This community service activity is focused on assisting the "Math Fun" activity which aims to increase the knowledge of the instructors of Sanggar Insan Emas Rungkut, Surabaya as well as motivate the students' interest in learning mathematics. "Math Fun" is a community service activity program carried out by mathematics lecturers assisted by IKIP Widya Darma Surabaya students, of course using an innovative approach in learning mathematics. Through this program, we seek to broaden the tutors' insight into mathematics learning and change students' perceptions of mathematics from initially being difficult and boring to becoming an interesting and fun mathematics subject. This service method uses a participatory method. The results of this program show that the "Math Fun" activity succeeded motivating students' interest in learning mathematics at SIER-Rungkut, Surabaya. Students begin to see mathematics as an interesting and relevant subject in their daily lives. Thus, this tutoring activity shows that with the right method, mathematics can be taught in a more interesting and inspiring way, providing a positive impact on students' mathematics learning.